Connecting Spiritual Rational Humanism: The Trend of Religious Moderation in the Modernization of Madrasah - Sri Bulan; M. Yunus Abu Bakar; Ah. Zakki Fuad; Hikmawati Rahayu (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
The rapid intellectual development of Islam in Indonesia has necessitated the modernization of  Islamic education, particularly in Madrasah Aliyah Negeri (MAN/ Public Islamic High School)  Insan Cendekia Pekalongan, which integrates spiritual rational humanism with religious  moderation. This study examines the connection between religious values and rational  modernization through the transformation of five core programs: digital madrasah, foreign  language development, adiwiyata madrasah, research madrasah, and homestay programs.  Employing a qualitative field research method, data was collected through in-depth interactive  communication with key stakeholders, including the head of the madrasah, deputy heads, and  research supervisors. The findings reveal that the rational-spiritual connection is manifested  through program modernization, which integrates multicultural values, tolerance, and local  wisdom into the madrasah’s academic environment. The modernization framework is inspired  by Habibie's intellectual and technological advancements, aiming to cultivate holistic human  development through the synergy of faith, science, and technology. This study highlights the  strategic role of religious moderation in balancing Islamic spirituality and rational thought,  enabling students to navigate contemporary educational challenges while maintaining their  cultural and religious identity. The implications of this research underscore the necessity of  curriculum transformation in Islamic education to enhance scientific literacy, critical thinking,  and social intelligence, thereby fostering a generation of Muslim scholars and professionals  who embody intellectual and ethical excellence. Future studies should explore the longitudinal  impact of these modernization programs on students' academic and socio-religious trajectories.